Microwave Radiometer Systems : Design and Analysis. - Skou, Niels (Artech House, 2006)
Thoroughly revising and updating an Artech House classic from 1989, this authoritative resource offers you a comprehensive and current understanding of radiometer systems and shows you how to design a system based on given specifications, taking into account both technical aspects and geophysical realities. The second edition contains a wealth of new material, including coverage of two of today's hottest microwave radiometry topics - polarimetric measurements and aperture synthesis. The book provides you with a complete explanation of radiometer sensitivity, and describes the concept of absolu.